Fault damage zones in mechanically layered rocks: The effects of planar anisotropy. Issue 8 (2nd August 2015) - Misra, Santanu; Ellis, Susan; Mandal, Nibir
Abstract This study shows how inherited strength anisotropy influences damage localization at both the tip and wall regions of a fault or fracture. We performed analogue and numerical compression experiments on transversely isotropic models with single and multiple cuts of finite length, simulating the propagation of preexisting faults and cracks in layered rock. The stress‐strain curves from the analogue experiments show a change in bulk yield behavior with fault inclination and anisotropy orientation with respect to the stress direction. Earlier isotropic models demonstrated a brittle (wing fracturing) to ductile (shear‐zone formation) transition as the fault angle (α) to the principal compression direction increased. The experiments with anisotropic models show patterns of damage localization change dramatically with the orientation of transversely isotropic planes (θ, measured with respect to principal extension direction). Under layer‐normal (θ = 0°) and layer‐parallel compression (θ = 90°), preexisting faults undergo significant reactivation when 0 < α < 90°, and fault slip eventually leads to mechanical instabilities within the anisotropic layering, causing damage zones in the tip regions. For layer‐normal (θ = 0°) compression, the damage processes involve intense extensional shear localization, whereas for layer‐parallel compression, contractional shear localization and tensile opening result in characteristic internal shear‐band structures. In contrast, for 0 < θ < 90°, the faults undergo little or no reactivation, irrespective of α. In this case, bulk compression leads to an interlayer slip‐mediated global deformation. Obliquely anisotropic models thus produce weak or no fault damage zones. We also show that the fault‐parallel principal damage localized at the tips can be coupled with transversely oriented, antithetic secondary damage in the wall regions. However, secondary damage develops predominantly when θ = 90°. Field examples of fault damage in anisotropic rocks and numerical experiments are in good accord with our experimental damage patterns.